KAJIAN YURIDIS TERHADAP PERATURAN BUPATI NOMOR 40 TAHUN 2014 TENTANG PEDOMAN PENANGANAN GELANDANGAN DAN PENGEMIS KABUPATEN JEMBER - Fery Mahardika; Lutfian Ubaidillah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Poverty remains a persistent challenge for developing countries, including Indonesia. Poverty is classified into two types: structural poverty, caused by government policies, and cultural poverty, stemming from societal habits. One manifestation of poverty is the existence of beggars and homeless individuals (Gepeng), which arises from both internal factors such as poverty and lack of skills, and external factors like unfavorable environmental conditions. This study focuses on the implementation of Jember Regent Regulation No. 40 of 2014 concerning the Guidelines for Handling Beggars and Homeless People in Lojejer Village, Jember Regency. The aim of this research is to examine the role of the government in addressing the issue of Gepeng in Lojejer Village. The research employs a legal and conceptual approach with a normative juridical type of research. The findings of this study are expected to provide theoretical contributions as references for academics and practical benefits for policymakers in addressing social issues related to beggars and homeless people in Jember Regency. It is hoped that this research will enhance social welfare in line with the mandate of Law No. 11 of 2009 on Social Welfare and Jember Regent Regulation No. 40 of 2014.